PpWRKY4 regulates chilling injury in peach fruit by activating PpVIN2 and accelerating sucrose metabolism - Yongyan, Wu; Shiyun, Zhang; Yi, Chen; Yingying, Wei; Feng, Xu; Phebe, Ding; Xingfeng, Shao (Elsevier B.V., 2025)
Among the vacuolar invertase (VIN) genes involved in sucrose metabolism within peach fruit, only PpVIN2 is sensitive to cold stress and is closely associated with both sucrose metabolism and cold stress. In this study, the PpWRKY4 gene, which responded to cold stress, was screened through cluster analysis of WRKY genes in peach fruit at cold stress and Reverse transcription - Quantitative Polymerase Chain Reaction (RT-qPCR) analysis of methyl jasmonate (MeJA)-treated fruit. Subcellular localization revealed that PpWRKY4 functions as a nuclear-localization protein. Further investigations using yeast one-hybridization (Y1H), electrophoretic mobility shift assay (EMSA), and dual-luciferase reporter (DLR) assay demonstrated that PpWRKY4 acts as a transcriptional activator for PpVIN2 promoter (PpVIN2pro). Transient transformation experiments of peach fruit showed that overexpression of PpWRKY4 not only increased the expression level of PpVIN2 but also enhanced VIN enzyme activity, thereby facilitating sucrose decomposition. To further explore the role of PpWRKY4, overexpressing PpWRKY4 transgenic Arabidopsis plants were constructed. These transgenic plants exhibited higher levels of AtVIN2 expression compared to wild-type (WT) plants, accompanied by reduced sucrose content. Interestingly, following exposure to low-temperature stress, the survival rate of the transgenic Arabidopsis was significantly lower than that of WT plants. Collectively, these findings suggested that PpWRKY4 influences sucrose metabolism and regulates the cold tolerance of peach fruit by activating PpVIN2.